Wnt 3a Protects Myocardial Injury in Elderly Acute Myocardial Infarction by Inhibiting Serum Cystatin C/ROS-Induced Mitochondrial Damage - Shen, Jian; Li, Ying; Jiao, Yang; Wang, Jihang; Hou, Xiaoling; Su, Yongkang; Liu, Bing; Liu, Henan; Sun, Zhijun; Xi, Qing; Fu, Zhenhong (Frontiers in Physiology, 2022)
Aging represents an independent risk factor affecting the poor prognosis of patients with acute myocardial infarction (AMI). This present research aimed to explore the molecular mechanism of myocardial injury in elderly AMI by animals and cells experiment. Our previous clinical study found the serum Cystatin C (Cys-C) increased in the elderly AMI population, while the mechanism underlying high Cys-C induced myocardial injury of AMI remains unclear. In the in-vitro study, we confirmed that Wnt/β-catenin could significantly reduce the expression of cytoplasmic Cys-C through transnuclear action, and highly attenuate the occurrence of mitochondrial oxidative stress injury induced via Cys-C /reactive oxygen species (ROS). Furthermore, the addition of exogenous Wnt3a and inhibition of Cys-C expression could effectively inhibit mitochondrial oxidative stress injury and relieve the acute myocardial hypoxia injury. These results indicate that Cys-C exerted damaging effects on the hypoxic aging cardiomyocyte through the ROS/mitochondrial signaling pathway. Inhibition of this pathway effectively reduced the apoptosis of aging cardiomyocytes. In the in-vivo study, we also explored the function of the Wnt/Cys-C pathway on the ischemic infarction heart. We confirmed that Wnt/β-catenin served as the upstream protective protein of this pathway, and the promotion of this pathway improved the cardiac structure and function of the elderly AMI mice effectively.